ANALISIS PERKEMBANGAN NILAI AGAMA-MORAL SISWA USIA DASAR (TERCAPAI) STUDI KASUS DI MI MA’ARIF BEGO - Iswatun Khoiriah; ifat nabilah; Suyadi Suyadi (Universitas Islam Negeri (UIN) Mataram, 2019)
The development of elementary school age children is a matter that must be guided, and guarded together by parents, teachers, and the community. All parties must be involved in maintaining and creating a good environment for the nation's next generation. This is due to many distorted phenomena committed by elementary age children, such as bullying, stealing, smoking, fighting, fighting parents and the most concerning is the case of free sex and drugs. Based on these phenomena, the development of religious and moral values of elementary age students is very appropriate and interesting to study. This research is intended to analyze the development of the religious and moral values of elementary age children achieved. This research is a descriptive qualitative study with data collection methods using interview techniques to obtain data from the informants or respondents who are the research subjects. In addition, researchers also conducted interviews with teachers and conducted literature reviews from various sources to supplement and sharpen data related to the topics discussed. The research subject to be studied was a Class VI student from MI Ma'arif Bego. The results showed that the factors supporting the achievement of children's religious-moral values on the subject there are 3 factors namely, internal / from within the child, family, school and environment. These three factors must support each other, supervise, remind, guide, set an example and take care of one another so as to create the next generation of people who are religiously religious and moral. As well as the achievement of the development of religious and moral values in elementary age students, it will alienate elementary age students from deviant behavior and things.